Analisis Kebutuhan Konsumen Hotel Savero Dengan Metode Quality Function Deployment (QFD) - Sofiani Sofiani (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This research was conducted to see the needs of hotel consumers by using the Quality Function Deployment (QFD) method at Hotel Savero. The purpose of using QFD in this study is to see consumer needs (customer needs) and corrective action (technical characteristics). In addition, indicators of consumer perceptions and perceptions as well as the gap between expectations and consumer perceptions and whether there are significant differences between expectations and perceptions. The data were processed using Quality Function Deployment (QFD. The results showed that there was a negative gap between expectations and perceptions as well as a significant difference between expectations and consumer perceptions.